Socioeconomic Status is Independently Associated with Overall Survival in Patients with Multiple Myeloma - Fiala, Mark A. (Leuk Lymphoma, 2015)
Population-based studies suggest that black patients with multiple myeloma (MM) have a higher mortality rate than white patients; however, other studies suggest this disparity is related to socioeconomic status (SES) rather than race. To provide clarity on this topic, we reviewed 562 patients diagnosed with MM at our institution. Patients with high-SES had a median OS of 62.8 months (mos) (95% CI 43.1–82.6 mos), compared to 53.7 mos (45.2–62.3 mos) and 48.6 mos (40.4–56.8 mos) for the middle and low-SES, respectively (p =0.015). After controlling for race, age, year of diagnosis, severity of comorbidities, stem cell transplant utilization, and insurance provider, patients with low-SES had a 54 percent increase in mortality rate relative to patients with high-SES. To support our findings, we performed a similar analysis of 45,505 patients with MM from the Surveillance Epidemiology and End Results-18 (SEER) database. Low-SES is independently associated with poorer OS in MM.